2012
DOI: 10.1186/1749-8546-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Phellinus linteus polysaccharide extracts against thioacetamide-induced liver fibrosis in rats: a proteomics analysis

Abstract: BackgroundThe hepatoprotective potential of Phellinus linteus polysaccharide (PLP) extracts has been described. However, the molecular mechanism of PLP for the inhibition of liver fibrosis is unclear. This study aims to investigate the molecular protein signatures involved in the hepatoprotective mechanisms of PLP via a proteomics approach using a thioacetamide (TAA)-induced liver fibrosis rat model.MethodsMale Sprague–Dawley rats were divided into three groups of six as follows: Normal group; TAA group, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Over the last few decades, in most countries the rate of people being treated with alternative therapy, particularly dietary supplements and herbal, has increased (29-38). Herbal medicine has fewer side effects and now is also recommended by the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, in most countries the rate of people being treated with alternative therapy, particularly dietary supplements and herbal, has increased (29-38). Herbal medicine has fewer side effects and now is also recommended by the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…P. linteus contains various bioactive substances, including polysaccharides and proteoglycans, which have been shown to exert anticancer and immune-regulatory properties [9] . Although most studies have focused on polysaccharides as active ingredients responsible for the antitumor effects of P. linteus [10][11][12] , our previous studies, interestingly, indicated that the anticancer activity of PB was observed in ethyl acetate extract, but not in boiled-water [8] . These observations suggested that the major anticancer constituent of PB might be retained in the nonpolar organic solvent fraction rather than in the polysaccharide-rich aqueous fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharide was given orally at a dose of 50 mg/kg BW twice a day from the beginning of the TAA treatment until the end of the experiment. The proteomics data indicate that P. linteus may be protective against TAA-induced liver fibrosis via regulation of oxidative stress pathways, heat shock pathways, and metabolic pathways for amino acids and nucleic acids(135) .Phellinus gilvus (Family: Hymenochaetaceae): Phellinus gilvus is well known as a source of antitumor and immunopotentiating polysaccharides and have been used as folk medicines for a variety of human ailments in several Asian countries for a long time. Park et al (2009) separated Downloaded by [New York University] at 03:hot aqueous extract of the basidiocarp and evaluated its hepatoprotective efficacy against CCl 4 induced liver injury in Sprague Dawley rats (136) .…”
mentioning
confidence: 99%